Influence of hydrogen on the elastic properties of nickel single crystal: A numerical and experimental investigation. (15th April 2018) - Hachet, G.; Metsue, A.; Oudriss, A.; Feaugas, X.
Abstract: A theoretical formalism based on density functional theory was conducted to examine the influence of hydrogen on the elastic constants of nickel at finite temperature. In this investigation, we also performed uniaxial tensile tests on < 001 > oriented nickel single crystals with different hydrogen concentrations. We highlighted large discrepancies between the elastic properties determined with these two approaches. Thus, further investigations were carried out on the influence of defects induced by the incorporation of hydrogen. Differential scanning calorimetry on samples charged with hydrogen showed that the vacancy concentration was in the same range as the hydrogen concentration. Moreover, voids around 2 nm in diameter were visible with transmission electron microscopy. Additional calculations were performed on nickel and nickel-hydrogen systems with vacancy, which confirmed that defects had a higher impact on the elastic constants of nickel than the solute. Finally, we used an analytical model derived from linear elastic theory to quantify the impact of vacancy clusters on the elastic constants. We reproduced the experimental degradation of < 001 > Young's modulus with increasing hydrogen concentration for spherical isotropic clusters with a diameter 10 times smaller than the voids observed with transmission electron microscopy. Graphical abstract: Image 1